Clinic-mycological spectrum of Candida infection in diabetic foot ulcers in a tertiary care hospital - Azam Moslemi; Tahereh Shokohi; Maryam Salimi; Leila Faeli; Lotfollah Davoodi; Zahra Kashi; Mahdi Abastabar; Iman Haghani; Sabah Mayahi; Seyed Reza Aghili (Current Medical Mycology)
Background and Purpose: In diabetic foot ulcers, if fungal agents, such as Candida species penetrate the cutaneous or depth of the ulcer, it can increase the wound severity and make it more difficult to heal. Materials and Methods: A cross-sectional study was performed on 100 diabetic patients with a foot ulcer from December 2019 to November 2020 in northern Iran. Patient data and wound grades were recorded in a questionnaire. Candida infection was confirmed by direct microscopic examination and culture. To identify the causative agent, polymerase chain reaction-restriction fragment length polymorphism using MspI enzyme and the partial amplification of hyphal wall proteins (HWP1) gene were performed.Results: Mean age of the participants was 62.1 ± 10.8 years old, and 95% of them had type 2 diabetes. Moreover, more than 83% of them had diabetes for a duration of 10 years. In addition, 59% of the patients were male, and 66% > of them had poor education levels. Besides, 99% of them were married, and 52% were rural. Furthermore, 95% of the participants had neuropathic symptoms and 88% used antibiotics. The HbA1C level was > 9% in 69% of them, and the mean ulcer grade of the patients was 2.6±1.05. Candida infection was detected in 13% of the deep tissue and 7% of the tissue surrounding the wound. The predominant Candida isolate was C. parapsilosis (71.5%) and C. albicans (14.3%). Infections caused by filamentous fungi were not detected. There was a statistically significant relationship between Candida infection and gender, rural lifestyle, HbA1C, and ulcer grade.Conclusion: Mycological evaluations of diabetic foot ulcers are often ignored. The present study revealed that C. parapsilosis is the most common causative agent of deepseated foot ulcer infection in these patients and may require specific treatment. Therefore, more attention of physicians to Candida infections, early diagnosis, and prompt treatment can help accelerate wound healing and prevent amputation.